Educational Counseling Programs for Students with Disabilities during the Pandemic - Maria Drossinou Korea (Budapest International Research and Critics University, 2020)
The present empirical and descriptive study aims to highlight the contribution of educational programs to the academic progress of adult students with Special Educational Needs and disabilities (SENs/Ds) during the pandemic period (World Health Organization, 2020 b). The main hypothesis investigated whether these interventions for learning problems helped them to manage the personal difficulties that hinder the smooth process of obtaining the degree. Data were collected with empirical descriptions according to the observation and the intervention methodology for SENs/Ds and were recorded with some protocols with physical presence or by distance learning. The pedagogical tool for the Special Educational Programs was applied with emphasis on the Targeted Individual Counseling Structured, Differentiated, Didactic Intervention without Exclusion interventions. The recordings followed the linear layout of the interventions that students receive at the University upon their request. The results showed that educational programs can temporarily relieve students in dealing with academic difficulties in work exams. Isolation, social distance and emotion management also proved to be extremely difficult for most students.